(Triphenylphosphine)copper hydride hexamer - S.F. Parker, ISIS (My University, 2014)
Inelastic Neutron Scattering spectrum of (Triphenylphosphine)copper hydride hexamer, [(C₆H₅)₃PCuH]₆, measured on the TOSCA instrument. Stryker’s reagent.
Keywords: TOSCA